Analisis Kinerja Pegawai berdasarkan Faktor Kepemimpinan, Motivasi, dan Disiplin Kerja (Studi pada UPTD Puskesmas Jeunieb Kabupaten Bireuen) - Wiza, Adilla; Ibrahim, Ibrahim (Singkite Journal, 2023)
The Regional Technical Implementation Unit (UPTD) of Jeunieb District, Bireuen Regency, is one of the public health units that is really needed considering that the area is far from the hospital in the capital city of Bireuen Regency. There are still various problems that occur in serving the needs of the community which causes the performance of medical and non-medical employees to be high and low. Many things influence the performance of Community Health Center employees, but this research tries to examine leadership factors, work motivation and employee work discipline. This research observed 81 employees with an instrument in the form of a closed questionnaire. This type of research uses associative descriptive and uses a path analysis model approach. The research results show: (1) The contribution of leadership factors, both direct and indirect, is 31.11% to increasing employee performance. (2) There is a significant influence between work motivation and work discipline on performance at 24.4% and 18.57% respectively. (3) Simultaneously the three predicted variables, namely leadership, motivation and employee work discipline, provide a positive contribution to efforts to increase employee performance by 16.10%.